ANALISIS KEBIJAKAN PEMERINTAH DAERAH DALAM PENGEMBANGAN ‘JAMINAN SOSIAL KESEHATAN SUMATERA SELATAN SEMESTA’ MENYAMBUT UNIVERSAL HEALTH COVERAGE - Misnaniarti Misnaniarti (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The ‘Jamsoskes Sumsel Semesta’ is a localprogram that offered free medical treatment for health servicesfor the people of South Sumatra who do not have healthinsurance. Meanwhile, starting in 2014, the national Governmentwill implement the Universal Health Coverage as mandated bythe Social Security Law. As insurance have a principle ofindemnity where there should not be a duplicate social security,there should be no society that is assured by the two programswith the aim of speculating to make a profit. This study aims toexplore the implementation of the expansion plan of ‘JamsoskesSumsel Semesta’ to pave the way to Universal Health Coveragein 2014 in South Sumatera.Methods: This study was a qualitative policy research withexploratory design. The focus are policy content, context,actors, and policy processes. Data were collected by in-depthinterviews and observation. Sources of information obtainedfrom five informants from the institution of Provincial HealthOffice, Planning and Regional Development Agency of SouthSumatra, and Provincial Government who selected bypurposive technique based on considerations of participationin Jamsoskes. The analysis used is the analysis of policy.Results and Discussion: Based on the results of study it isfound that the South Sumatra provincial government willcontinue to provide the Jamsoskes program in 2014 as it is,managed by the Health Office. Some of the considerations arefor efficiency and flexibility and that it does not include all thepeople. Also, in the Presidential Decree No. 12 of 2013, thenational government still provides opportunities for local schemeto grow until 2019. Some development is done in Jamsoskesincluding improving the quality and quantity of health careproviders. Preparations are coordinated with Social SecurityAgency about number of contribution beneficiaries. One ofthe challenges is that the community rather go to the hospitaldirectly so it can interfere with the referral system.Conclusion: There has not been a lot of development effortundertaken by local government onJamsoskes in preparationfor the 2014 to welcome Universal Health Coverage. The SouthSumatra provincial government should develop further theservices under Jamsoskes as adjustments in welcoming theimplementation of the second phase of the National HealthInsurance.Keywords: Policy, Health Insurance, Jamsoskes, Efficiency